2014
DOI: 10.4236/ojoph.2014.41003
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Cup-to-Disc Ratio in Children

Abstract: Purpose: The aim of this study is early detection of increased cup to disc ratio and a survey study of cup-disc ratio in Egyptian children age group less than 15 years. Methods: Three hundred and eighty-two (382) children were enrolled in this study. They were classified into three age groups; infants' Group (1) from 0 -2 years, preschool Group (2) from 2 -6 years and school children Group (3) from 6 -15 years old. C/D ratio was measured for each child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The normal CDR is less than 0.1 in the first year of life and it can increase up to 0.3 by 15 years of age [ 24 ]. The high mean CDR of 0.73 from our study population signifies advanced disease presentation and the need for urgent surgical intervention to improve visual prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The normal CDR is less than 0.1 in the first year of life and it can increase up to 0.3 by 15 years of age [ 24 ]. The high mean CDR of 0.73 from our study population signifies advanced disease presentation and the need for urgent surgical intervention to improve visual prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a child, the scleral canal is distensible, and cupping in PCG proceeds more rapidly and is occasionally reversible (Quigley 1977; Quigley 1982; Robin 1979). A cup/disc ratio greater than 0.3 also may be indicative of glaucoma (normal 0 mm to 0.1 from birth to two years and 0.1 mm to 0.2 from two to six years) (Amer 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The pterygium, lacrimal intubation, lid surgeries and the limbal mass were done by the surgical team in the central hospital we found that the trachomatous complications 81%were the majority of the problems solved by minor surgeries . In revision of the various reports of the WHO about blindness worldwide 17 and other studies in Egypt [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , it is clear that The Egyptian Oasis is not far from the estimated rate of blindness as well as the prevalence of eye disease as shown in our results.…”
Section: Resultsmentioning
confidence: 99%
“…The screening study was also a way of training residents and interns about working with such large number of population. [19][20][21] Working as an assistant in the medical and surgical divisions of the campaign provided a great experience of learning for younger generation. They examined most of the varieties of ophthalmic diseases having the chance to acquire knowledge from the attending professor or consultant.…”
Section: Resultsmentioning
confidence: 99%